2020
DOI: 10.1161/circresaha.119.315807
|View full text |Cite
|
Sign up to set email alerts
|

Lgr4 Governs a Pro-Inflammatory Program in Macrophages to Antagonize Post-Infarction Cardiac Repair

Abstract: Rationale: Macrophages are critically involved in wound healing following myocardial infarction (MI). Lgr4, a member of leucine-rich repeat-containing G protein-coupled receptor (LGR) family, is emerging as a regulator of macrophage-associated immune responses. However, the contribution of Lgr4 to macrophage phenotype and function in the context of MI remains unclear. Objective: To determine the role of macrophage Lgr4 in MI and to dissect the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 54 publications
1
84
0
Order By: Relevance
“…Although Fosl1 is well-known as an essential transcription factor that constitutes the AP-1 compound with c-fos and c-jun in the development of many diseases of injury [24,[53][54][55], its role in the occurrence and progression of SCI has not yet been elucidated. By exploring the GSE45006 and analyzing the datasets, we learned that Fosl1 expression was signi cantly upregulated following SCI at 1 d and 3 d postoperation.…”
Section: Discussionmentioning
confidence: 99%
“…Although Fosl1 is well-known as an essential transcription factor that constitutes the AP-1 compound with c-fos and c-jun in the development of many diseases of injury [24,[53][54][55], its role in the occurrence and progression of SCI has not yet been elucidated. By exploring the GSE45006 and analyzing the datasets, we learned that Fosl1 expression was signi cantly upregulated following SCI at 1 d and 3 d postoperation.…”
Section: Discussionmentioning
confidence: 99%
“…Osteocalcin‐Cre (Ocn‐Cre) C57BL/6 mouse line used in the current study has been described ( 30,31 ) and was purchased from The Jackson Laboratory (Bar Harbor, ME, USA). Lgr4 flox/flox mice were generated as described ( 18,32,33 ) and were backcrossed with C57BL/6 mice for at least nine generations to obtain a pure C57BL/6 background. Mice were housed in a specific pathogen‐free environment with a constant temperature (22 ± 2°C) and humidity (50–70%), and a fixed light cycle.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown that LGR4, rather than LGR5, is indispensable in mammalian early hematopoiesis by downstream TGF-beta signaling [ 93 ]. In addition, LGR4 may play a critical role in wound healing, fibrosis, and inflammation [ 94 , 95 ], particularly through the NF-κB signaling [ 33 , 96 ]. LGR4 also takes part in the innate immune response by modulating the TLR2/4 pathway and regulating monocyte to macrophage differentiation [ 97 , 98 ].…”
Section: Lgr4 In Normal Tissuesmentioning
confidence: 99%